Move: Durational Dance-Making as We Age - Nikolai, Jennifer (Frontiers in Sports and Active Living, 2022)
Abstract Dance making and moving supports positive aging approaches to aesthetic, cultural, and social meanings, shaping dancers' lives. My perspective is informed, by making dance as a durational, sustained practice in the life of a long-life mover. Positioned as a practice-oriented researcher, I am surrounded by inspiring authors and artists who embrace maturity with improvisational making. This perspective piece reflects on making Move; a durational practice-oriented research process. Move contextualises durational elements I associate with the life of a mover. My writing, companions improvising with my hand-held camera in isolation, in my neighbourhood on Tāmaki Makaurau / Auckland's North Shore. This perspective piece opens a process I refer to as a camera-dancer dyad; a duet between dancer and camera; making in isolation, as we age. Furthermore, by embracing the accessibility of everyday recording devices as dancing partners, dance making with mobile cameras becomes a playful partnership with a long life.